Efficiency analysis for active rectifier in more electric aircraft (MEA) generator - Lim, Sin Guang (Nanyang Technological University, 2021)
There has been an increasing trend for transport electrification to address the environmental degradation issues caused by the increasing usage of fossil fuels as a result of rising air travel demand prior to the COVID-19 pandemic. This leads to an increase in demand for efficient energy conversion to reap the full advantages of transport electrification where power electronics play a crucial role. Traditionally, the Insulated Gate Bipolar Transistors (IGBTs) are widely preferred in the industry due to its simplicity and lower costs. However, the main drawback of the IGBTs is the higher switching losses, which makes it difficult for usage in high frequency switching applications. On the other hand, the Metal-Oxide-Semiconductor-Field-Effect Transistors (MOSFETs) are characterised by lower switching losses. Nonetheless, there are circumstances in which the IGBTs have a better performance than the MOSFETs. Therefore, this project will look into the comparisons of the performance of IGBTs and MOSFETs in the application of active rectifiers. In addition, a holistic comparison will be conducted between the efficiency of the two-level and three level topologies. Accordingly, the three-level topology provides a more efficient alternative to the two-level topology at higher switching frequencies. Therefore, this project will incorporate the IGBTS and MOSFETs into the two-level and three-level topologies to analyse the power losses. Furthermore, stability analysis will be performed on the controllers of the three-phase rectifier. The purpose is to study the performance of the controllers to maximise the efficiency of the rectifiers. In this analysis, further fine tuning will be done to achieve the desired overall performance of the rectifier. In summary, this project will conduct a detailed analysis on power losses of silicon IGBTs and silicon carbide MOSFETs through simulations. Various hardware will be configured to incorporate it into the lab prototype for future experimental verification. The objectives of this project are to investigate the power losses of the semiconductors in various topologies and identify the semiconductor and topology that will bring the maximum efficiency of the rectifier.